Perspectives on corporate governance - Kieff, F. Scott; Paredes, Troy; Cambridge eBooks (Cambridge : Cambridge University Press, 2010)
The events that began with the collapse of Enron, WorldCom, Tyco, and Adelphia and continued into the financial crisis of 2008 teach us an important lesson: corporate governance matters. Although it is widely acknowledged that good corporate governance is a linchpin of good corporate performance, how can one improve corporate governance and its impact on corporate and overall economic performance. This book offers a diverse and forward-looking set of approaches from experts, covering the major areas of corporate governance reform and analyzing the full range of issues and concerns. Written to be both theoretically rigorous and grounded in the real world, the book is well suited for practicing lawyers, managers, lawmakers, and analysts, as well as academics conducting research or teaching a wide range of courses in law schools, business schools, and economics departments.
Introduction / F. Scott Kieff and Troy A. Paredes -- The trouble with boards / Lawrence E. Mitchell -- Rediscovering board expertise : legal implications of the empirical literature / Lawrence A. Cunningham -- The CEO and the board : on CEO overconfidence and institutionalizing dissent in firms / F. Scott Kieff and Troy A. Paredes -- Pay without performance : overview of the issues / Lucian A. Bebchuk and Jesse M. Fried -- Supersize pay, incentive compatibility, and the volatile shareholder interest / William W. Bratton -- 'Say on pay' : cautionary notes on the U.K. experience and the case for muddling through / Jeffrey N. Gordon -- Shareholder activism in the Obama era / Stephen M. Bainbridge -- After Dura : causation in fraud-on-the-market actions / Merritt B. Fox -- From boardroom to courtroom to newsroom : the media and the corporate governance scandals / Kathleen F. Brickey -- How Delaware law can support better corporate governance / James D. Cox -- Federalism versus federalization : preserving the division of responsibility in corporation law / E. Norman Veasey, Shawn Pompian, and Christine Di Guglielmo -- Regulatory differences in bank and capital market regulation / Hideki Kanda -- European corporate governance after five years with Sarbanes-Oxley / Rainer Kulms -- Epilogue : Three secular trends of corporate law / Joel Seligman.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Corporate governance -- Law and legislation -- United States; Corporation law -- United States; Electronic books